PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KINERJA ORGANISASI PERANGKAT DAERAH - Selva Temalagi; Nirwana Nirwana; Aini Indrijawati (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the influence of human resource competency and internal control systems on organizational performance in the Regional Apparatus Organizations (OPD) of Central Maluku Regency. This study used a quantitative approach with a survey method. Data were collected by distributing questionnaires to 40 respondents, who were civil servants in the OPD of Central Maluku Regency. The data analysis technique used was multiple linear regression analysis with hypothesis testing using the t-test. The results showed that human resource competency did not significantly influence organizational performance, therefore the first hypothesis was rejected. This finding indicates that individual civil servant competency does not necessarily translate directly into improved organizational performance, which is suspected to be influenced by structural factors such as inefficient work processes, a suboptimal performance evaluation system, and limited work facilities. Conversely, the internal control system proved to have a positive and significant effect on organizational performance, therefore the second hypothesis was accepted. This indicates that the implementation of an effective internal control system, which encompasses the control environment, risk assessment, control activities, information and communication, and monitoring, can improve OPD performance